The Relationship between Childhood Experiences of Submissiveness, External shame and Paranoia in a Portuguese Student Sample - Lopes, Barbara (2013)
Paranoia has been conceptualised as a form of defence against perceived threat that is associated to internal shame, issues of rank and history of trauma in clinical populations. We aimed to explore whether a student sample would show external and internal shame with paranoid ideation and if this is related to childhood experiences of threat. A total of 165 college students were given a battery of scales measuring non-clinical paranoid ideation and experiences of paranoia, submission, external and internal shame, forms of self-blame vs. blame others and childhood memories of a threatening family environment. Results supported our hypotheses. Portuguese students acknowledge experiences of paranoia and those that acknowledged paranoid experiences presented statistically significantly more shame and childhood experiences of threat and submissiveness towards significant others than the ones that do not acknowledge having paranoia. A linear regression with a LASSO model also showed that external shame was the only significant predictor of paranoia which supports new literature about the importance of shame memories in shaping paranoia. Clinical implications are inferred suggesting the importance of teaching students to manage feelings of shame as a way of preventing the onset of paranoid ideation.